2021
DOI: 10.1021/acs.jnatprod.1c00835
|View full text |Cite
|
Sign up to set email alerts
|

Irilone, a Red Clover Isoflavone, Combined with Progesterone Enhances PR Signaling through the Estrogen and Glucocorticoid Receptors

Abstract: Trifolium pratense L. (red clover) is a popular botanical supplement used for women’s health. Irilone isolated from red clover previously demonstrated progestogenic potentiation activity. In this study, irilone enhanced progesterone signaling was determined to not occur due to post-translational phosphorylation or by reducing progesterone receptor (PR) protein levels but instead increased PR protein levels in T47D breast cancer cells, which could be blocked by estrogen receptor (ER) antagonists, suggesting an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…According to our data, food consumption is similar in pregnant and lactating females, so the higher levels of irilone in the lactating does could be a consequence of a lower use of this compound by lactating females (increasing its excretion). In this context, more interesting is the oestrogenic potential (Lutter et al, 2014) and recent progestogenic activity found of this metabolite, which can enhance the progesterone signalling (Austin et al, 2021). It is suggested that the irilone has a synergic effect on progesterone and is capable of binding to the receptors of this hormone, enhancing its effects.…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, food consumption is similar in pregnant and lactating females, so the higher levels of irilone in the lactating does could be a consequence of a lower use of this compound by lactating females (increasing its excretion). In this context, more interesting is the oestrogenic potential (Lutter et al, 2014) and recent progestogenic activity found of this metabolite, which can enhance the progesterone signalling (Austin et al, 2021). It is suggested that the irilone has a synergic effect on progesterone and is capable of binding to the receptors of this hormone, enhancing its effects.…”
Section: Discussionmentioning
confidence: 99%